If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -9) = 11 Reorder the terms: (-9 + 2x) = 11 Remove parenthesis around (-9 + 2x) -9 + 2x = 11 Solving -9 + 2x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 2x = 11 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = 11 + 9 2x = 11 + 9 Combine like terms: 11 + 9 = 20 2x = 20 Divide each side by '2'. x = 10 Simplifying x = 10
| (4b^2-4b-4)-(-5b^2+3b+7)= | | 5(x+2)=25x | | 5m+8/7=4 | | 2.1n-5.31=18 | | 10x^2+7x= | | (3y^2+8y-4)-(-4y+2)= | | 9y-5=-14 | | 69*x=9000000000 | | -5=c/7 | | 3(2x+4)=6 | | (6x^2+8)-(3x^2-12)= | | 6x+3=23x | | -6x+2(5x+1)=6 | | (5x^2+8)-(11x^2-3)= | | (5x^2-2x-2)-(-3x^2-3x-8)= | | -6x-3(2x-2)=-6 | | 3y=9 | | (7t^3+2t)-(-7t^3-4t+5)= | | (7x+7)-(9x-6)= | | -3x-4(4x+11)=-5 | | -2(4+-11)=-18 | | -9r/4 | | 4x-6(2x+4)=-8 | | 9x-85+49/70=x | | -3(3t-7)=66 | | 4x+4(-3x-2)=8 | | y^2+8=12 | | 5x+11=-19 | | 5x+2=-53 | | 9(3G+6)=40.5 | | 5x+10=30findx | | 6(x+4)=3(x+16) |